FINANCIAL LITERACY AND INFLUENCE OF PSYCHOSOCIAL FACTORS - Bashir, Taqadus; Arshad, Asba; Nazir, Aleena; Afzal, Naghmana (European Scientific Journal, ESJ, 2013)
Financial literacy is individual’s ability to understand financial terms and instruments. In Pakistan, individuals simply know that they are depositing money in various institutions in order to get more wealth in name of profit. They don’t know what exactly they are doing and they are ignorant about the functions and existence of financial markets. This scenario generates the need to study and measure financial literacy in Pakistan. The study used data from National Savings Centers of Pakistan which has been used first time for research purpose in Pakistan. Ordinary least square regression was used to analyze relationship of psychosocial factors with financial literacy. After assessing basic and advanced financial knowledge, individuals of Pakistan were found to be financially illiterate and there existed a positive relationship between financial literacy and other psychosocial factors which were hopelessness, religiosity, financial satisfaction, retirement plan intention and risk preference. Financial literacy was also positively related to age, qualification, marital status and occupation as older, highly qualified, married and business persons were more financially literate. Financial literacy had significant positive relationship with gender, hopelessness and retirement plan intention. This study has implications for researchers, academicians and policy makers.